PRODUKTIVITAS USAHATANI PADI SAWAH LEBAK DENGAN PEMBIAYAAN USAHATANI SISTEM TUNAI DAN YARNEN DI KECAMATAN SANGA DESA KABUPATEN MUSI BANYASIN - Fitriyana, Gusti (Universitas Muhammadiyah Palembang, 2021)
This study aims to find out how much farming productivity is in lowland paddy fields with cash and yarnen systems, the difference in productivity between farmers who buy production facilities with cash and yarnen systems and to find out how much income the farmers who buy production inputs with cash and yarnen systems earn. Simple random sampling methode is used in this study. The results of this study indicate that the productivity level of lowland paddy rice farming with the yarnen system is higher then cash system, where the average productivity of the yarnen system is 5,106 Kg/ha while the cash system is 4,583 Kg/ha. There is a significant difference between them. The average income of farmers with a cash system is Rp. 16,755,810 while the average income of farmers with the yarnen system is Rp. 13,130,817.